Liquid metal bridging confined ultra-thin MXene-based water-based paint, preparation method and application

CN122941302APending Publication Date: 2026-10-20BEIJING WANCHUAN SCIENCE & TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611130071.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0002]工业锅炉是电力、化工、供暖等领域核心热能动力设备,其受热面在高温、腐蚀、飞灰冲蚀工况下易出现高温腐蚀、磨损、结焦结垢等问题,严重影响设备寿命与运行效率

Benefits of technology

导热系数达 10–18 W/(mK),较传统涂层提升 20 倍以上,显著降低热阻。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This disclosure discloses a liquid metal-bridged confined ultrathin MXene-based waterborne composite coating, its preparation method, and its application. By weight, it comprises: 8-18 parts of confined ultrathin MXene nanosheets SiO2@MXene, 2-6 parts of liquid metal microspheres, 10-20 parts of Ag@BNNS heterojunction, 25-45 parts of waterborne silica sol-organosilicon hybrid resin, 5-12 parts of wear-resistant filler, 5-15 parts of corrosion-resistant filler, 1-4 parts of chitosan, 1-4 parts of coupling agent, 0.2-0.8 parts of dispersant stabilizer, 0.5-3 parts of additives, and deionized water to the remainder of 100 parts. This disclosure utilizes SiO2 physical confinement, liquid metal interlayer filling, and Ag@BNNS interface bridging to collaboratively construct a multi-level "point-surface-line" heat conduction network. The coating achieves a thermal conductivity of 10-18 W / (mK) and possesses high hardness, strong adhesion, wear resistance, corrosion resistance, and anti-scaling properties. When applied to the heating surfaces of industrial boilers, it can reduce heat transfer resistance, inhibit coking and scaling, and improve boiler thermal efficiency, thereby achieving energy conservation and emission reduction. This coating is water-based, environmentally friendly, simple to process, and suitable for large-scale production and for enhancing heat transfer protection on industrial boiler heating surfaces.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure belongs to the field of functional nanocomposite coating materials and industrial energy-saving and environmental protection technology, specifically relating to a liquid metal bridging confined ultrathin MXene-based waterborne composite coating and its preparation method and application, which is particularly suitable for the protection of the heating surface of industrial boilers, enhancing heat transfer and saving energy and reducing emissions. Background Technology

[0002] Industrial boilers are core thermal power equipment in fields such as power, chemical industry, and heating. Their heating surfaces are prone to problems such as high-temperature corrosion, wear, coking and scaling under high temperature, corrosion and fly ash erosion conditions, which seriously affect the service life and operating efficiency of the equipment.

[0003] Traditional protective coatings generally have low thermal conductivity, which increases heat transfer resistance and reduces boiler thermal efficiency after application. Solvent-based coatings have high VOC emissions and poor environmental performance. MXene materials have advantages such as high thermal conductivity and high specific surface area, but they also have drawbacks such as easy agglomeration, easy oxidation at high temperatures, high interfacial thermal resistance, and difficulty in forming continuous heat conduction pathways. Therefore, they cannot directly meet the integrated requirements of "high thermal conductivity + protection + anti-scaling" under boiler operating conditions.

[0004] Currently, there is a lack of water-based environmentally friendly coatings that combine high thermal conductivity, wear resistance, corrosion resistance, and prevention of coking and scaling, making it difficult to achieve synergistic protection of heated surfaces and enhanced heat transfer. Therefore, this disclosure provides a liquid metal-bridging confined ultrathin MXene-based water-based coating to solve the aforementioned technical problems. Summary of the Invention

[0005] The purpose of this disclosure is to overcome the shortcomings of the prior art and provide a liquid metal bridging confinement ultrathin MXene-based waterborne composite coating. Through SiO2 physical confinement, liquid metal interlayer filling, and Ag@BNNS interface bridging, a multi-level heat conduction network is constructed to achieve high thermal conductivity, high wear resistance, strong corrosion resistance, and anti-scaling properties. It is waterborne, environmentally friendly, and has good temperature resistance, making it suitable for long-term service in industrial boilers.

[0006] Another objective of this disclosure is to provide a method for preparing the above-mentioned coatings, which has a stable process and can be mass-produced.

[0007] Another objective of this disclosure is to provide the application of the above-mentioned coatings in the protection and heat transfer enhancement of the heating surfaces of industrial boilers.

[0008] To achieve the above objectives, the present disclosure adopts the following technical solution: A liquid metal bridging confined ultrathin MXene-based waterborne composite coating, the components of which are as follows (by weight): Confined ultrathin MXene nanosheets: 8-18 parts Liquid metal microspheres: 2-6 parts Ag@BNNS heterojunction: 10-20 parts Aqueous silica sol-organosilicon hybrid resin: 25-45 parts Wear-resistant filler: 5-12 parts Corrosion-resistant filler: 5-15 parts Chitosan: 1-4 parts Silane coupling agent: 1-4 parts Dispersant stabilizer: 0.2-0.8 parts Additives: 0.5-3 parts Deionized water: balance to 100 parts The confined ultrathin MXene nanosheets are constructed using one or more strategies among SiO2 physical confinement, liquid metal interlayer confinement filling, and Ag@BNNS interface confinement bridging.

[0009] Optionally, the confinement strategy for constructing the confined ultrathin MXene nanosheets is selected from: Physical confinement of SiO2 nanoparticles: Surface-aminated SiO2 electrostatically self-assembles with MXene to form a SiO2@MXene core-shell structure, enabling the MXene sheets to be oriented and aligned. Liquid metal interlayer confinement filling: Gallium indium alloy EGaIn or gallium indium tin alloy liquid metal infiltrates into the micro-voids between MXene layers to form a continuous three-dimensional thermally conductive network (EGaIn@MXene or GalnSn@MXene). Ag@BNNS heterojunction interface confined bridging: Silver nanoparticles are loaded in situ onto the surface of BNNS to reduce the thermal resistance of the filler-filler interface through point-to-surface contact (Ag@BNNS@MXene). Optionally, the MXene nanosheets are selected from Ti3C2T x Ti2CT x V2CT x One or more of the following; sheet thickness 1nm-5nm, lateral dimension 0.5μm-5μm.

[0010] Optionally, the liquid metal microspheres are gallium indium alloy EGaIn or gallium indium tin alloy; with a particle size of 50 nm - 200 nm.

[0011] Optionally, the Ag@BNNS heterojunction is prepared by in-situ chemical reduction, with silver nanoparticles of 10 nm-50 nm in diameter uniformly loaded on the BNNS surface to form a point-to-surface heterostructure.

[0012] Optionally, the wear-resistant filler is selected from one or more of nano-SiC, nano-Al2O3, and boron carbide; and / or, the corrosion-resistant filler is selected from one or more of zinc molybdate, zinc phosphate, and aluminum tripolyphosphate; and / or, the dispersing stabilizer is sodium tartrate; and / or, the silane coupling agent is KH550 or KH560; and / or, the additives include defoamers, leveling agents, and thickeners.

[0013] This disclosure also proposes a method for preparing a coating, comprising the following steps: (1) MXene etching and stripping: The Al layer of the MAX phase was etched by LiF+HCl etching method, followed by centrifugal washing, ultrasonic stripping, graded centrifugation, and standing to obtain MXene nanosheet slurry; (2) Confined structure pre-assembly: a) Aminated SiO2 nanoparticles were added to a mixed MXene slurry and ultrasonically self-assembled to obtain a SiO2@MXene core-shell structure; b) Ag@BNNS heterojunctions were prepared by liquid phase exfoliation and in-situ chemical reduction; c) The EGaIn liquid metal was ultrasonically dispersed in an aqueous solution containing a surfactant to obtain a liquid metal microsphere dispersion; (3) Coating preparation: a) Confined ultrathin MXene nanosheets, Ag@BNNS, wear-resistant filler, and dispersant stabilizer were added to deionized water and ultrasonically dispersed. b) Add liquid metal microsphere dispersion under inert gas protection and disperse ultrasonically; c) Grind until D90 ≤ 10 μm; d) Add water-based silica sol-organosilicon hybrid resin and mix at low speed; e) Add sodium bicarbonate to adjust the pH to 8.0-8.5, and stir the reaction. f) Add the anti-corrosion filler, silane coupling agent, and additives in sequence, adjust the pH and viscosity, and filter out the material.

[0014] Optionally, the dispersion and addition of liquid metal in steps (2)c and (3)b are carried out under Ar gas protection; ultrasonic power is 200-500 W, time is 30-60 min, and temperature is controlled by ice bath.

[0015] This disclosure also proposes an industrial boiler in which the heating surface is coated with the coating proposed in this disclosure.

[0016] Optionally, the industrial boiler includes a coal-fired boiler, a biomass boiler, a waste heat boiler, or a waste incineration boiler; the heating surface includes one or more of the following: water-cooled wall, superheater, reheater, economizer, and air preheater.

[0017] Optionally, the coating is sprayed / brushed onto the boiler heating surface, the substrate is sandblasted to Sa2.5 grade with a roughness of 40-70 μm; the dry film thickness is 80-150 μm; and the coating is cured at room temperature for 24 h, then cured at 80-120 ℃ for 2-4 h or at room temperature for 24 h.

[0018] The beneficial effects of this disclosure are as follows: Thermal conductivity reaches 10–18 W / (m K), which is more than 20 times higher than traditional coatings, significantly reducing thermal resistance.

[0019] Hardness ≥5H, adhesion grade 0, wear loss reduced by more than 95%, salt spray resistance ≥1000 h.

[0020] Low surface energy and high thermal conductivity uniformity work together to suppress coking and scaling, significantly extending the coking and cleaning cycle.

[0021] Boiler thermal efficiency is improved by 3-8%, achieving energy saving and carbon reduction.

[0022] It is a water-based system with low VOCs, safe construction, and can withstand temperatures up to 400℃. The process can be scaled up. Attached Figure Description

[0023] Figure 1 Low-magnification and high-magnification scanning electron microscope images of the coating prepared in Example 1 of this disclosure; Figure 2 Low-magnification and high-magnification scanning electron microscope images of the coating prepared in Comparative Example 3 of this disclosure; Figure 3 The infrared spectrum of the coating prepared in Example 1 of this disclosure; Figure 4 Photographs of the coating prepared in Example 1 of this disclosure after being immersed in 1 mol / L NaOH solution for different numbers of days; Figure 5 Photographs of the coating prepared in Example 1 of this disclosure after being immersed in a 1 mol / L HCl solution for different number of days; Figure 6 This is a schematic diagram of the cyclic thermal shock resistance test of the coating prepared in Embodiment 1 of this disclosure; Figure 7 Photographs of the coating prepared in Example 1 of this disclosure after undergoing cyclic abrasion resistance testing; Figure 8 is a schematic diagram of the thermal conductivity test of the coating prepared in Example 1 of this disclosure; Figure 9 is a schematic diagram of the thermal conductivity of the coating prepared in Example 1 of this disclosure. Detailed Implementation

[0024] To enable those skilled in the art to better understand the technical solutions of this disclosure, the disclosure will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0025] This disclosure and methods for implementing it can be better understood by referring to the following detailed description of exemplary embodiments and accompanying drawings. However, this disclosure can be implemented in many different forms and should not be construed as limited to the exemplary embodiments set forth herein. The same reference numerals may always refer to the same elements. In the drawings, the thickness of layers and regions may be exaggerated for clarity.

[0026] To make the objectives, technical solutions, and advantages of this disclosure clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this disclosure. Furthermore, the technical features involved in the various embodiments of this disclosure described below can be combined with each other as long as they do not conflict with each other.

[0027] This disclosure proposes a liquid metal-bridged confined ultrathin MXene-based waterborne composite coating, the components of which, by weight, include the following components: Confined ultrathin MXene nanosheets (SiO2@MXene): 8~18 parts; Liquid metal microspheres: 2-6 parts; Ag@BNNS heterojunction: 10-20 parts; Aqueous silica sol-organosilicon hybrid resin: 25-45 parts; Wear-resistant filler: 5-12 parts; Corrosion-resistant filler: 5-15 parts; Chitosan: 1-4 parts; Silane coupling agent: 1-4 parts; Dispersant stabilizer: 0.2~0.8 parts; Additives: 0.5-3 parts; Deionized water: balance to 100 parts; Among them, confined ultrathin MXene nanosheets refer to nanosheets or assemblies of which are extremely thin (usually ≤ 100 nm), structurally ordered and have excellent performance, prepared by confining two-dimensional MXene materials in a specific space (such as nanochannels, interlayer gaps or substrate surfaces) through physical or chemical means.

[0028] Specifically, the confined ultrathin MXene nanosheets disclosed herein are constructed using one of the following strategies: SiO2 physical confinement, liquid metal interlayer confinement filling, and Ag@BNNS interface confinement bridging. For example: (a) Physical confinement of SiO2 nanoparticles: Surface-aminated SiO2 and MXene electrostatically self-assemble to form a SiO2@MXene core-shell structure, which makes the MXene sheets oriented and aligned. (b) Liquid metal interlayer confinement filling: Gallium indium alloy EGaIn or gallium indium tin alloy liquid metal penetrates into the micro-voids between MXene layers to form a continuous three-dimensional heat conduction network; (c) Ag@BNNS heterojunction interface confined bridging: Silver nanoparticles are loaded in situ on the surface of BNNS to reduce the thermal resistance of the filler-filler interface through point-to-surface contact.

[0029] Among them, MXene nanosheets are selected from Ti3C2T x Ti2CT x V2CT x One or more of the following; sheet thickness 1nm-5nm, lateral dimension 0.5μm-5μm; Among them, the liquid metal microspheres are, for example, gallium indium alloy EGaIn or gallium indium tin alloy. For gallium indium tin alloy: gallium mass fraction is 70%-80%, indium is 20%-30%, and tin content is 5%~10%; the particle size of the liquid metal microspheres is 50 nm-200 nm.

[0030] Among them, the Ag@BNNS heterostructure is prepared by in-situ chemical reduction method, with silver nanoparticles of 10 nm-50 nm in size uniformly loaded on the BNNS surface to form a point-to-surface heterostructure.

[0031] Among them, the wear-resistant filler is selected from one or more of nano SiC, nano Al2O3, and boron carbide; the corrosion-resistant filler is selected from one or more of zinc molybdate, zinc phosphate, and aluminum tripolyphosphate; the dispersing stabilizer is one of sodium tartrate, sodium polyacrylate, and polyvinylpyrrolidone; the silane coupling agent can be selected from KH550 or KH560; the additives include defoamer, leveling agent, and thickener.

[0032] On the other hand, this disclosure proposes a method for preparing a liquid metal-bridged confined ultrathin MXene-based waterborne composite coating, comprising the following steps: (1) MXene etching and stripping: For example, the Al layer of the MAX phase is etched by LiF+HCl etching, followed by centrifugation, washing, ultrasonic exfoliation, and fractional centrifugation to obtain a multilayer and few-layer mixed MXene slurry. After standing, the supernatant can be taken to obtain a single-layer ultrathin MXene nanosheet. (2) Confined structure pre-assembly: a) Aminated SiO2 nanoparticles were added to a mixed MXene slurry and ultrasonically self-assembled to obtain a SiO2@MXene core-shell structure; b) Ag@BNNS heterojunctions were prepared by liquid phase exfoliation and in-situ chemical reduction; c) Ultrasonically disperse EGaIn or gallium indium tin alloy liquid metal in an aqueous solution containing a surfactant to obtain a liquid metal microsphere dispersion; (3) Coating preparation: a) Add SiO2@MXene, Ag@BNNS, wear-resistant filler, and dispersant stabilizer to deionized water and disperse using ultrasound; b) Add liquid metal microsphere dispersion under inert gas protection and disperse ultrasonically; c) Grind until D90 ≤ 10 μm; d) Add water-based silica sol-organosilicon hybrid resin and mix at low speed (80-100 rpm). e) Add sodium bicarbonate to adjust the pH to 8.0-8.5, and stir to react for 1 hour; f) Add the anti-corrosion filler, silane coupling agent, and additives in sequence, adjust the pH and viscosity, and filter out the material.

[0033] In step (2)c and step (3)b, the dispersion and addition of liquid metal are carried out under Ar gas protection; the ultrasonic power is 200-500 W, the time is 30-60 min, and the temperature is controlled by an ice bath.

[0034] Example 1 A liquid metal bridging confined ultrathin MXene-based waterborne composite coating comprises the following components by weight: 12 parts SiO2@MXene, 4 parts EGaIn, 15 parts Ag@BNNS, 35 parts waterborne silica sol-organosilicon hybrid resin, 8 parts nano SiC, 1 part sodium tartrate, 2 parts chitosan, 9 parts zinc molybdate, 2 parts KH560, 1 part additive, and the balance being deionized water.

[0035] Among them, water-based silica sol-organosilicon hybrid resin (commercial product, Jin Huan brand) acts as an adhesive in the coating.

[0036] The coating consists of 12 parts SiO2@MXene, 4 parts EGaIn, 15 parts Ag@BNNS, and 8 parts nano-SiC, forming the main powder components. After film formation, these components provide efficient heat transfer, wear resistance, and corrosion protection. Sodium tartrate and chitosan act as stabilizers in the coating system and help enhance intermolecular forces, increasing the adhesion between the coating and the substrate. Zinc molybdate provides corrosion protection; 2 parts KH560 improves interfacial compatibility and stabilizes the coating; additives include a drier and a leveling agent (commercially available products).

[0037] In this implementation, Ti3C2T is selected as the MXene nanosheet.x The wear-resistant filler is nano-SiC, and the dispersant and stabilizer is sodium tartrate.

[0038] Use 1 M sodium bicarbonate solution as a pH adjuster to adjust the pH to 8.0-8.5.

[0039] Zinc molybdate was selected as the corrosion-resistant filler, with drier and leveling agents as additives. The drier was manufactured by Lishengyuan Chemical Products, and the leveling agent by Honghua Chemical Co., Ltd. The addition of the corrosion-resistant filler significantly increased viscosity due to increased internal friction, and its own acidity or alkalinity affected the pH environment of the system. With the addition of a silane coupling agent, the viscosity of the system decreased by improving the wetting and dispersibility of the filler surface and breaking up particle agglomeration.

[0040] Preparation: The coating was prepared according to the above method and sprayed onto boiler-like steel. After drying, the coating film thickness was approximately 120 μm, and it was cured at 100 °C for 2 h.

[0041] Tested performance: Thermal conductivity 15.6 W / (m) K); adhesion grade 0; hardness 6H; salt spray resistance 1200 h; wear rate reduction 96.5%; coking inhibition rate 75%.

[0042] like Figure 1 As shown, low-magnification and high-magnification electron micrographs of the coating prepared in Example 1 applied to the surface of a copper sheet are displayed. Figure 1 The coating exhibits a continuous and dense substrate phase, with no obvious pores, peeling, or large-scale defects on the surface. The coating demonstrates excellent film-forming properties and consistent macroscopic uniformity. Fine particle / fibrous structures are clearly visible, forming a composite morphology of the substrate and dispersed phases. High-magnification scanning electron microscopy images confirm the presence of nanoscale roughness in the coating, which significantly enhances its thermal conductivity and wear resistance.

[0043] like Figure 3 The image shown is an infrared image of the coating prepared in Example 1. It can be seen that at 460 cm⁻¹... -1 This is the bending vibration peak of the Si-O bond, a fundamental characteristic of siloxane structures. 800 cm⁻¹ -1 It is the symmetric stretching vibration peak of the Si-O-Si bond, corresponding to the bonding mode of bridging oxygen in the siloxane network. Figure 3 1080 cm -1 The peak at 1460 cm⁻¹ is the asymmetric stretching vibration peak of the Si-O-Si bond, exhibiting the highest intensity and being a hallmark feature of the siloxane crosslinking network. This demonstrates the existence of a continuous Si-O-Si bond inorganic network structure in the coating. -1 The peak represents the CH bending vibration of the methylene group, indicating the alkyl chain in the coated silane coupling agent. 2850 cm⁻¹ -1-2920 cm -1 The peaks at 1630 cm⁻¹ represent the symmetric / asymmetric stretching vibrations of the methylene group, further confirming the presence of the organic alkyl component and providing evidence for the organosilicon coating. -1 This is the bending vibration peak of HOH, corresponding to the presence of physically adsorbed water or water of crystallization in the coating. 3420 cm⁻¹ -1 The peak represents the stretching vibration of OH bonds in the coating, originating from two sources: incompletely cross-linked silanol groups in the coating and OH bonds formed by water adsorbed on the coating surface. The broad peak morphology is a typical characteristic of hydrogen-bonded hydroxyl groups.

[0044] The continuous, uniform, and dense deposition on the coating surface endows it with excellent resistance to alkali corrosion. After being placed in a 1 mol / L NaOH solution for different number of days, the coating surface remained uniform and continuous, without exhibiting typical corrosion failure phenomena such as blistering, peeling, flaking, or powdering. The color showed no significant darkening, yellowing, or localized color difference, and no visible corrosion pits, cracks, or pinholes were observed. Figure 4 As shown.

[0045] like Figure 5 As shown, after the coating was placed in a 1 mol / L HCl solution for different number of days, the overall surface of the coating remained uniform and continuous, and no typical corrosion failure phenomena such as blistering, peeling, flaking, or powdering were observed. The color did not darken, yellow, or show local color differences, and no visible corrosion pits, cracks, or pinholes were observed.

[0046] The above phenomena prove that the coating has excellent resistance to acid and alkali corrosion.

[0047] like Figure 6 As shown, the prepared coating was subjected to cyclic thermal shock resistance testing. The test method was as follows: a coated stainless steel bowl was placed on a heating furnace and heated, and then the hot bowl was quickly immersed in room temperature water for rapid cooling (coated side facing cold water), completing one thermal shock cycle. After repeated cyclic thermal shock tests of 20 and 100 times, no peeling or flaking was found on the coating surface, proving that the coating has excellent thermal shock resistance.

[0048] like Figure 7 As shown, the prepared coating was subjected to abrasion resistance tests. After being scratched 20, 100, and 200 times, the coating surface showed no obvious scratches, peeling, or flaking, indicating that the coating has good abrasion resistance.

[0049] like Figure 8As shown, the thermal conductivity of the prepared coating was tested. Compared to the uncoated stainless steel bowl, the coated bowl exhibited superior thermal conductivity. On an electric furnace of the same power, regardless of the heating time, the water temperature in the coated bowl was consistently higher than that in the pure stainless steel bowl. The time required for the water in the coated bowl to reach 90 °C was 5 minutes and 5 seconds, while the time required for the pure stainless steel bowl to reach 90 °C was 7 minutes and 23 seconds. It can be inferred that the thermal conductivity of the stainless steel bowl was improved by 45%–50% after coating. Finally, the water in the coated bowl boiled more rapidly and vigorously. The test results are as follows. Figure 9 As shown.

[0050] Example 2 Components: 10 parts EGaIn@MXene, 5 parts EGaIn, 5 parts Ag@BNNS, 35 parts waterborne silica sol-organosilicon hybrid resin, 12 parts nano SiC, 0.5 parts sodium tartrate, 5 parts chitosan, 10 parts zinc molybdate, 4 parts KH560, 1 part additives, water balance.

[0051] Tested performance: Thermal conductivity 18.2 W / (m) K); thermal conductivity retention rate of 92% after aging at 400 ℃ for 500 h; adhesion grade 0.

[0052] Example 3 Components: 8 parts Ag@BNNS@MXene, 6 parts liquid metal, 10 parts Ag@BNNS, 38 parts hybrid resin, 12 parts nano Al2O3, 0.6 parts sodium tartrate, 1 part chitosan, 10 parts zinc molybdate, 2 parts KH560, 2 parts additives, water balance.

[0053] Tested performance: Thermal conductivity 14.2 W / (m) K); adhesion grade 0; hardness 5H; salt spray resistance 800 h; coking inhibition rate 65%.

[0054] Example 4 Components: 18 parts SiO2@MXene, 2 parts liquid metal, 5 parts Ag@BNNS, 36 parts hybrid resin, 10 parts boron carbide, 10 parts zinc phosphate, 0.8 parts sodium tartrate, 2 parts chitosan, 4 parts KH560, 3 parts additives, water balance.

[0055] Tested performance: Thermal conductivity 17.5 W / (m) K); adhesion grade 0; hardness 7H; salt spray resistance 1100 h; coking inhibition rate 80%.

[0056] Comparative Example 1 (using pure MXene nanosheets instead of confined MXene structures) The formulation is the same as in Example 1, using pure MXene nanosheets instead of confined MXene structures. The thermal conductivity is only 8.8 W / (m²). K), with unconfined thermal conductivity and a good structure.

[0057] Comparative Example 2 (without liquid metal) The formulation is the same as in Example 1, but without EGaIn. The thermal conductivity is only 5.8 W / (m²). K), the heat-conducting network is discontinuous.

[0058] Comparative Example 3 (without Ag@BNNS, using pure BNNS) The formulation is the same as in Example 1, except that an equal amount of BNNS replaces Ag@BNNS. Thermal conductivity: 7.2 W / (m²). K), high interface thermal resistance.

[0059] Comparative Example 4 The formulation is the same as in Example 1, but without SiC. Thermal conductivity: 8.58 W / (m²). K), lacks anti-friction ability and is easily detached under the scouring of particles.

[0060] like Figure 2 The image shows low-magnification and high-magnification SEM images of the coating prepared in Comparative Example 3. Through-cracks can be observed on the surface, which are macroscopic defects formed by stress release during the coating preparation or drying process. These defects allow water molecules to penetrate, affecting the coating's corrosion resistance and wear resistance. Numerous agglomerated particles / fillers are distributed on the surface, dispersed in clusters within the substrate. This uneven distribution indicates poor filler dispersion in the coating, making it prone to forming localized defects.

[0061] Comparative Example 5 The formulation is the same as in Example 1, but without chitosan. Thermal conductivity: 15.53 W / (m²). The thermal conductivity of the coating was not significantly affected (K), but compared with Example 1, the coating's erosion resistance decreased.

[0062] Comparative Example 6 The formulation is the same as in Example 1, but without zinc molybdate. Thermal conductivity: 13.62 W / (m²). The thermal conductivity of the coating was not significantly affected (K), but it was still reduced to some extent. However, compared with Example 1, the corrosion resistance of the coating was significantly reduced.

[0063] Comparative Example 7 (Commercially available water-based epoxy anti-corrosion coating) Thermal conductivity 5.38 W / (m K), has no anti-scaling function, and increases thermal resistance after coating.

[0064] Industrial Application Examples Example 1: Water-cooled wall of a 35 t / h circulating fluidized bed boiler Coating area approximately 200 m² 2 It uses high-alkali coal. After 8 months of operation: coking volume decreased by 70%, the coking cycle was extended from 1 month to 4 months; flue gas temperature decreased by 20 ℃; thermal efficiency increased by 4.4%; coal consumption for power generation decreased by 2.2 g / kWh, with a cumulative coal saving of approximately 520 tons.

[0065] Example 2: Superheater of a 130 t / h pulverized coal boiler Coating area approximately 80 m 2 After 6 months of operation: steam temperature increased by 4 ℃, desuperheating water consumption decreased by 1.2 t / h; thermal efficiency increased by 3.1%, and annual coal savings were approximately 300 tons.

[0066] Table 1 Summary of thermal conductivity of coatings under different preparation conditions

[0067] Table 2 Summary of various properties of coatings under different preparation conditions

[0068] The coating performance testing methods involved in Tables 1 and 2 are as follows: (1) Thermal conductivity test Several identical stainless steel bowls were used as heating media. Coatings prepared using different methods were applied to the bottom of each bowl as treatment groups, while bowls without any coating served as blank controls. 500 ml of water was added to each bowl simultaneously, and they were placed on identical hot stoves for heating. Thermometers were inserted into each bowl at the same time. A stopwatch was used to record the time required for the water in each bowl to reach the specified temperature.

[0069] (2) Measurement of actual drying time of coating Referring to the GB / T1728 standard, place a piece of filter paper on the surface of the coated membrane, and then use a 200g weight to press it onto the membrane surface. After a certain period of time, remove the weight. If the filter paper can fall freely, the coating can be considered to have achieved actual drying. Continue to record the time required to achieve actual drying.

[0070] (3) Corrosion resistance test The coated stainless steel bowl was placed in a 1M HCl solution for different time periods. The corrosion resistance time of the coating was measured by weighing, and the peeling time of the coating quality was recorded to measure the corrosion resistance performance of the coating.

[0071] (4) Abrasion resistance test The stainless steel bowl with a coating is repeatedly scratched with sharp tweezers. The change in mass of the stainless steel bowl before and after scratching is measured within a certain period of time to measure the wear resistance of the stainless steel bowl.

[0072] (5) Impact resistance test The impact resistance of the coating was tested using a drop hammer impact test. Samples were prepared according to standard requirements, with dimensions of 100 × 100 mm. The center impact point and non-impact surfaces were marked on the sample. The sample was placed in a standard laboratory environment (room temperature, 50 ± 10% relative humidity) for a specified time (usually ≥ 24 h) to eliminate the influence of temperature and humidity. The hammer was raised to a preset height and locked. The hammer was released via command on the control panel, allowing it to fall freely and impact the sample. The force-time or force-displacement curves were automatically recorded by the instrument.

[0073] (6) High temperature resistance test The coating on the iron sheet is placed in a preset high-temperature environment and heated for a specified time. The mass change of the coating sample before and after is weighed to measure the high-temperature resistance of the coating sample.

[0074] Compared with the prior art, the beneficial effects of this disclosure are as follows: The coating prepared according to the embodiments of this disclosure has a thermal conductivity of 10-18 W / (m²). K), which is more than 20 times higher than traditional coatings, significantly reducing thermal resistance.

[0075] The coating prepared according to the embodiments of this disclosure has a hardness ≥5H, an adhesion grade of 0, a wear loss reduction of more than 95%, and salt spray resistance ≥1000 h.

[0076] The coating prepared according to the embodiments of this disclosure has low surface energy and high thermal conductivity uniformity, which synergistically inhibits coking and scaling, and significantly extends the coking cleaning cycle.

[0077] The coating prepared according to the embodiments of this disclosure, when applied to a boiler, improves the boiler's thermal efficiency by 3-8%, achieving energy saving and carbon reduction.

[0078] The coating prepared according to the embodiments of this disclosure is an aqueous system with low VOCs, safe construction, temperature resistance up to 400℃, and the process can be scaled up.

[0079] The embodiments described above are merely preferred embodiments of this disclosure. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Various modifications and improvements made to the technical solutions of this disclosure by those skilled in the art without departing from its spirit should fall within the protection scope defined by the claims of this disclosure.

Claims

1. A liquid metal-bridged confined ultrathin MXene-based waterborne composite coating, characterized in that, The following components are included by weight: Confined ultrathin MXene nanosheets: 8-18 parts; Liquid metal microspheres: 2-6 parts; Ag@BNNS heterojunction: 10~20 parts; Aqueous silica sol-organosilicon hybrid resin: 25~45 parts; Wear-resistant filler: 5-12 parts; Corrosion-resistant filler: 5-15 parts; Chitosan: 1-4 parts; Silane coupling agent: 1-4 parts; Dispersant stabilizer: 0.2~0.8 parts; Additives: 0.5-3 parts; Deionized water: balance to 100 parts; The confined ultrathin MXene nanosheets are constructed using strategies such as SiO2 confined intercalation, liquid metal interlayer confined filling, or Ag@BNNS interface confined bridging.

2. The coating according to claim 1, characterized in that, The confinement strategy for constructing the confined ultrathin MXene nanosheets is selected from one of the following structures: Physical confinement of SiO2 nanoparticles; electrostatic self-assembly of surface-aminated SiO2 with MXene to form a SiO2@MXene core-shell structure, enabling MXene sheets to be oriented and aligned. Liquid metal interlayer confinement filling: Gallium indium alloy EGaIn or gallium indium tin alloy liquid metal penetrates into the micro-voids between MXene layers to form a continuous three-dimensional heat-conducting network; Ag@BNNS heterojunction interface confined bridging: Silver nanoparticles are loaded in situ onto the surface of boron nitride nanosheets (BNNS) to reduce the thermal resistance of the filler-filler interface through point-to-surface contact.

3. The coating according to claim 1 or 2, characterized in that, The MXene nanosheets are selected from Ti3C2T x Ti2CT x V2CT x One or more of the following; sheet thickness 1 nm - 5 nm, lateral dimension 0.5 μm - 5 μm.

4. The coating according to claim 1 or 2, characterized in that, The liquid metal microspheres are gallium indium alloy EGaIn or gallium indium tin alloy GalnSn; the particle size is 50 nm - 200 nm.

5. The coating according to claim 1 or 2, characterized in that, The Ag@BNNS heterojunction was prepared by in-situ chemical reduction, with silver nanoparticles of 10 nm-50 nm in diameter uniformly loaded on the BNNS surface to form a point-to-surface heterostructure.

6. The coating according to claim 1 or 2, characterized in that, The wear-resistant filler is selected from one or more of nano-SiC, nano-Al2O3, and boron carbide; and / or, the corrosion-resistant filler is selected from one or more of zinc molybdate, zinc phosphate, and aluminum tripolyphosphate; and / or, the dispersing stabilizer is sodium tartrate; and / or, the silane coupling agent is KH550 or KH560; and / or, the additives include defoamers, leveling agents, and thickeners.

7. A method for preparing the coating according to any one of claims 1-6, characterized in that, Includes the following steps: (1) MXene etching and stripping: The Al layer of the MAX phase was etched by LiF+HCl etching, followed by centrifugal washing, ultrasonic stripping, and fractional centrifugation to obtain ultrathin MXene nanosheet slurry; (2) Confined structure pre-assembly: a) Aminated SiO2 nanoparticles were added to MXene nanosheet slurry and ultrasonically self-assembled to obtain a SiO2@MXene core-shell structure; or, b) Ag@BNNS heterojunctions were prepared by liquid-phase exfoliation and in-situ chemical reduction, then MXene nanosheet slurry was added, followed by ultrasonic self-assembly to obtain Ag@BNNS@MXene; or, c) Disperse liquid metal ultrasonically in an aqueous solution containing a surfactant to obtain a liquid metal microsphere dispersion; add MXene nanosheet slurry and ultrasonically self-assemble to obtain EGaIn@MXene or GalnSn@MXene; (3) Coating preparation: a) Confined ultrathin MXene nanosheets, Ag@BNNS, wear-resistant filler, and dispersant stabilizer were added to deionized water and ultrasonically dispersed. b) Add liquid metal microsphere dispersion under inert gas protection and disperse ultrasonically; c) Grind until D90 ≤ 10 μm; d) Add water-based silica sol-organosilicon hybrid resin and mix at low speed; e) Add sodium bicarbonate to adjust the pH to 8.0-8.5, and stir the reaction. f) Add the anti-corrosion filler, silane coupling agent, and additives in sequence, adjust the pH and viscosity, and filter out the material.

8. The preparation method according to claim 7, characterized in that, In steps (2)c and (3)b, the dispersion and addition of liquid metal are carried out under Ar gas protection; ultrasonic power is 200-500 W, time is 30-60 min, and ice bath temperature is controlled.

9. An industrial boiler, characterized in that, The heating surface of the industrial boiler is coated with the coating described in any one of claims 1-6.

10. The industrial boiler according to claim 9, characterized in that, The industrial boiler includes a coal-fired boiler, a biomass boiler, a waste heat boiler, or a waste incineration boiler; the heating surface includes one or more of the following: water-cooled wall, superheater, reheater, economizer, and air preheater.